Application of Nanotechnology in a Novel Air Purifier for Remediation of Airborne Pathogen and to Prevent the Spread of COVID-19 - Nabarun Ghosh; Shaily Goyal; Aubrey Howard; Prabir Banerjee; Jay Vitale (European Scientific Journal, ESJ, 2023)
The spread of COVID-19 occurs via airborne transmission. With a constant and variable spread of COVID-19, indoor air-quality has become a major concern all over the world. People who are infected with COVID can release particles and droplets of respiratory fluids that contain the SARS CoV-2 virus into the air when they exhale (e.g., quiet breathing, speaking, singing, exercise, coughing, sneezing). Once infectious droplets are exhaled, they move outward from the person (the source) into the surrounding environment; these droplets carry the virus and transmit infection. Indoors, the very fine droplets and particles will continue to spread through the air in the room or space and can accumulate. Harmful pathogenic organisms like fungi, bacteria and viruses, as the one responsible for causing contagious diseases like the ongoing pandemic of COVID-19 can also be successfully destroyed and neutralized. We have developed and studied the efficiency of the AFL Mini Sanifier II® in a simulated environment of a fiberglass chamber using various types of meters to assess the suspended particulate matter (PM) in the ambient air. We also report the development of a novel face mask that was assessed for safety measures and further improvement by the researchers in the West Texas A&M University. The mask is user friendly and portable, equipped with a small internal fan that supplies a continuous air to the user preventing the suffocating effect caused by the other masks. The novel mini air purifier is equipped with the advanced nanotechnology that cleans and sanitizes both the air and surfaces and subsequently has been shown to reduce common allergy, asthma and hay fever related symptoms. This mask and the mini air purifier function in an advanced way to combat all forms of airborne pathogens including the bacteria, viruses, mold spores and harmful Volatile Organic Compounds (VOC) present in the air.